miR-181d/RBP2/NF-κB p65 Feedback Regulation Promotes Chronic Myeloid Leukemia Blast Crisis - Zhou, Minran; Yin, Xiaolin; Zheng, Lixin; Fu, Yue; Wang, Yue; Cui, Zelong; Gao, Zhenxing; Wang, Xiaoming; Huang, Tao; Jia, Jihui; Chen, Chunyan (Frontiers in Oncology, 2021)
Background: Chronic myeloid leukemia (CML) is a malignant clonal proliferative disease. Once it progresses into the phase of blast crisis (CML-BP), the curative effect is poor, and the fatality rate is extremely high. Therefore, it is urgent to explore the molecular mechanisms of blast crisis and identify new therapeutic targets. Methods: The expression levels of miR-181d, RBP2 and NF-κB p65 were assessed in 42 newly diagnosed CML-CP patients and 15 CML-BP patients. Quantitative real-time PCR, Western blots, and cell proliferation assay were used to characterize the changes induced by overexpression or inhibition of miR-181d, RBP2 or p65. Luciferase reporter assay and ChIP assay was conducted to establish functional association between miR-181d, RBP2 and p65. Inhibition of miR-181d expression and its consequences in tumor growth was demonstrated in vivo models. Results: We found that miR-181d was overexpressed in CML-BP, which promoted leukemia cell proliferation. Histone demethylase RBP2 was identified as a direct target of miR-181d which downregulated RBP2 expression. Moreover, RBP2 inhibited transcriptional expression of NF-κB subunit, p65 by binding to its promoter and demethylating the tri/dimethylated H3K4 region in the p65 promoter locus. In turn, p65 directly bound to miR-181d promoter and upregulated its expression. Therefore, RBP2 inhibition resulting from miR-181d overexpression led to p65 upregulation which further forwarded miR-181d expression. This miR-181d/RBP2/p65 feedback regulation caused sustained NF-κB activation, which contributed to the development of CML-BP. Conclusions: Taken together, the miR-181d/RBP2/p65 feedback regulation promoted CML-BP and miR-181d may serve as potential therapeutic target of CML-BP.